Que peuvent entendre des enfants français d’aujourd’hui dans le conte des frères Grimm « Le Roi-grenouille ou Henri-de-fer » ? - Sève, Pierre (Ondina - Ondine, 2018)
This paper is dealing with the interpretative work of 10 and 11 years old pupils. If they are at first surprised by the violent relations between the frog and the princess, they further discover a rational and highly moral explanation of this violence. However they don’t fully understand the episode of the loyal servant. In the end, their thoughts on this tale do not differ much of the critics’ work. Keywords: original tale – literary reception – childhood – primary school